Monetary Policy Analysis in Practice - a Conditional Forecasting Approach - Ida Wolden Bache; Leif Brubakk; Anne Sofie Jore; Junior Maih; Jon Nicolaisen (Norges Bank, 2010)
In this paper we provide a broad outline of the forecasting and policy analysis system adopted at Norges Bank.
hdl:11250/2507753
Keywords: 330